Do Electronic Health Records Help or Hinder Medical Education? - Peled, Jonathan U. (Public Library of Science, 2009)
Background to the debate: Many countries worldwide are digitizing patients' medical records. In the United States, the recent economic stimulus package (“the American Recovery and Reinvestment Act of 2009”), signed into law by President Obama, includes $US17 billion in incentives for health providers to switch to electronic health records (EHRs). The package also includes $US2 billion for the development of EHR standards and best-practice guidelines. What impact will the rise of EHRs have upon medical education? This debate examines both the threats and opportunities.